RECOMMENDATIONS ON THE USE OF INNOVATIVE METHODS IN THE INTEGRATION PROCESSES IN THE MOTHER TONGUE AND READING LITERACY CLASSES IN PRIMARY GRADES" - Karimov Oybek Abdunazarovich, Khudoykulova Hilola Mamayunusovna (American Journals, 2023)
This article provides information on "recommendations on the use of innovative methods in the integration processes in the mother tongue and reading literacy classes in primary grades".
Keywords: Primary classes, literacy, lesson, integration process, innovation, pedagogy, reading